Evaluation of concentration and dispersion of functionalized carbon nanotubes in aqueous media by means of Low Field Nuclear Magnetic Resonance. (March 2017) - Porrelli, Davide; Cok, Michela; Abrami, Michela; Bosi, Susanna; Prato, Maurizio; Grassi, Mario; Paoletti, Sergio; Donati, Ivan
Abstract: Dispersions of functionalized carbon nanotubes (fx -CNTs) have been analyzed by means of Low Field Nuclear Magnetic Resonance measurements (LF-NMR). This technique showed that the presence of the fx -CNTs strongly influences the structuring of the water molecules. Thereupon, the water transversal relaxation rate (r2 ) can be used to get information about the concentration of the CNTs in aqueous dispersion and their aggregation tendency. Finally, the effect of the addition of an anionic polyelectrolyte, namely alginate, on aqueous dispersion of CNTs was explored by using LF-NMR, which revealed different dependence of r2 from CNT concentration, depending on the type and charge of fx -CNTs. Graphical abstract: